Acetylshikonin, A Novel CYP2J2 Inhibitor, Induces Apoptosis in RCC Cells via FOXO3 Activation and ROS Elevation. (9th March 2022) - Lim, Heui Min; Lee, Jongsung; Yu, Seon Hak; Nam, Myeong Jin; Cha, Hyo Sun; Park, Kyungmoon; Yang, Yung-Hun; Jang, Kyu Yun; Park, See-Hyoung
Abstract : Acetylshikonin is a shikonin derivative originated from Lithospermum erythrorhizon roots that exhibits various biological activities, including granulation tissue formation, promotion of inflammatory effects, and inhibition of angiogenesis. The anticancer effect of acetylshikonin was also investigated in several cancer cells; however, the effect against renal cell carcinoma (RCC) have not yet been studied. In this study, we aimed to investigate the anticarcinogenic mechanism of acetylshikonin in A498 and ACHN, human RCC cell lines. MTT (3-(4, 5-Dimethylthiazol-2-yl)-2, 5-Diphenyltetrazolium Bromide), cell counting, and colony forming assay showed that acetylshikonin induced cytotoxic and antiproliferative effects in a dose- and time-dependent manner. Cell cycle analysis and annexin V/propidium iodide (PI) double staining assay indicated the increase of subG1 phase and apoptotic rates. Also, DNA fragmentation was observed by using the TUNEL and comet assays. The intracellular ROS level in acetylshikonin-treated RCC was evaluated using DCF-DA. The ROS level was increased and cell viability was decreased in a dose- and time-dependent manner, while those were recovered when cotreated with NAC. Western blotting analysis showed that acetylshikonin treatment increased the expression of FOXO3, cleaved PARP, cleaved caspase-3, -6, -7, -8, -9, γ H2AX, Bim, Bax, p21, and p27 while decreased the expressions of CYP2J2, peroxiredoxin, and thioredoxin-1, Bcl-2, and Bcl-xL. Simultaneously, nuclear translocation of FOXO3 and p27 was observed in cytoplasmic and nuclear fractionated western blot analysis. Acetylshikonin was formerly identified as a novel inhibitor of CYP2J2 protein in our previous study and it was evaluated that CYP2J2 was downregulated in acetylshikonin-treated RCC. CYP2J2 siRNA transfection augmented that apoptotic effect of acetylshikonin in A498 and ACHN via up-regulation of FOXO3 expression. In conclusion, we showed that the apoptotic potential of acetylshikonin against RCC is mediated via increase of intracellular ROS level, activation of FOXO3, and inhibition of CYP2J2 expressions. This study offers that acetylshikonin may be a considerable alternative therapeutic option for RCC treatment by targeting FOXO3 and CYP2J2.